Relations Between Leadership Style and Communication Patterns with Effective Performance of Representative Livestock Owner Force Case: Farm School in Bojonegoro District - Darmawan, Musa; Saleh, Amiruddin (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2017)
Leader is a personÂ who believed by group members to guide and reach the common goals. A leader cannot be separated from leadership style that owned and applied to group. The leadership style also determine whether the agreed common goals can be reach or not, in terms of effectiveness group members themselves, how alert are they, whether they motivated and many factors among the group performance effectiveness. Communication Patterns is a process that designed to ease the communication process sustainability. The research purpose is to identify the influence of leadership style of Representative Livestock Owner Force (GPPT) contained Public School of Animal Husbandry (SPR) on theperformanceÂ effectiveness. Data analysis used descriptive statistic analysis (frequency, presentation, average and cross tabulation), and inferential statistic analysis with Spearman rank coefficient corelation test. The research result in research location disposed democratic and communication pattern that applied to small communication group. The result of the research showed that there is significance positive relation between democratic leadership style with performance effectiveness in time discipline indicator. It means better democratic leadership style that applied, higher time discipline applied in performance effectiveness. Between communication pattern and performance effectiveness there is no relation.Â Keywords : communication patterns, leadership style, performance effectiveness, public school of animal husbandry, representative livestock owner force===============================================ABSTRAK Pemimpin adalah orang yang dipercaya oleh anggota kelompok untuk mampu membimbing dan mencapai tujuan bersama yang telah disepakati. Pemimpin tak lepas dari gaya kepemimpinan yang diterapkan kepada sebuah kelompok. Gaya kepemimpinan juga menentukan berhasil atau tidak mencapai tujuan bersama yang telah disepakati, dilihat dari efektivitas anggota kelompoknya itu sendiri, seberapa siaga mereka, apakah mereka termotivasi, dan masih banyak faktor dari efektivitas kinerja ini. Pola komunikasi merupakan sebuah proses yang dirancang untuk mempermudah keberlangsungan proses komunikasi. Tujuan penelitian adalah mengidentifikasi sejauh mana gaya kepemimpinan yang diterapkan oleh anggota Gugus Perwakilan Pemilik Ternak (GPPT) dalam lembaga Sekolah Peternakan Rakyat (SPR) ini terhadap efektivitas kinerjanya. Penelitian didesain sebagai sensus deskriptif korelasional dengan pendekatan penelitian kuantitatif. Analisis data berupa analisis statistik deskriptif (frekuensi, persentasi, rata-rata dan tabulasi silang), dan analisis statistik inferensial dengan uji koefisien korelasi rank Spearman. Hasil penelitian menunjukkan, bahwa kepemimpinan di GPPT cenderung bergaya demokratik dan pola komunikasi yang diterapkan komunikasi kelompok kecil. Gaya kepemimpinan demokratik berkorelasi positif signifikan dengan efektivitas kinerja pada indikator disiplin waktu. Artinya, semakin pengurus GPPT bergaya kepemimpinan demokratik, maka semakin tinggi disiplin waktu yang diterapkan dalam efektivitas kinerja. Pada pola komunikasi dengan efektivitas kinerja tidak terdapat hubungan yang signifikan.Kata Kunci : efektivitas kinerja, gaya kepemimpinan, gugus perwakilan pemilik ternak, pola komunikasi, sekolah peternakan rakyat